Reflections on student leadership: the future of the creative industry - Nurul Nabila Junaidi,; Mohammad Danial Mohd Razali,; Faisal Zulhumadi,; Nur Marissa Vee Senap, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper explores leadership development in the context of the creative industry. The motivation behind this study lies in recognising the vital role that leadership plays in driving innovation, fostering collaboration, and navigating the complex and evolving landscape of the creative industry. The main issue addressed is the need for effective leadership practices that enable this industry to thrive and adapt to the changing dynamics of the global market. The methodology involved a comprehensive review of existing literature on leadership theories and practices, coupled with qualitative data collected through interviews with industry professionals and students in creative industry management programs. The study's results revealed vital leadership attributes and competencies required to lead successfully in the creative industry, including adaptability, visionary thinking, collaborative skills, and a deep understanding of technological advancements. The implications of this research contribute to the body of knowledge by providing insights and recommendations for leadership development programs tailored to the creative industry, ultimately equipping future leaders with the skills and mindset necessary to drive innovation and sustainability in this dynamic industry. Keywords: Leadership Development, Student Leadership, Creative Industry, Future Leaders, Universiti Utara Malaysia (UUM)